Features of economic diversification in rural areas for sustainable development - Allahverdiyeva, L.M.; Кurmanalina А.А.; Tasmaganbetov А.B.; Zhumatayeva , B.A. (BUKETOV BUSINESS REVIEW, 2019)
The article deals with the features of sustainable development of rural areas in the context of national and regional policy of the Republic of Kazakhstan. According to the authors, demographic, social, environmental and institutional factors should be taken into account when determining the level of rural development. The authors concentrate upon legislative and regulatory acts of the Republic of Kazakhstan on the development of rural areas and agriculture. In this article, it is noted that the main purpose of diversification of rural areas is their sustainable socio-economic development and improvement of the quality of living standards. Social and economic factors that contribute to the strengthening of the urbanization process are analysed by the authors. The article illustrates some changes in the structure of economic sectors (crop, livestock and other services) of rural areas of the Republic of Kazakhstan over the past five years. The authors identified following basic potential of rural areas for economic diversification: cheap land and natural resources; low-cost labor resources; natural landscapes for the development of tourism, recreation and other services. The diversification of the rural economy is associated with the development of non-agricultural activities, which in turn reduces the dependence of the economy on the results of agricultural production; contributes to the development of entrepreneurship; creates new jobs.